2001
DOI: 10.4049/jimmunol.166.9.5464
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of TCR Signaling by CD5

Abstract: Current data indicate that CD5 functions as an inhibitor of TCR signal transduction. Consistent with this role, thymocyte selection in TCR transgenic/CD5−/− mice is altered in a manner suggestive of enhanced TCR signaling. However, the impact of CD5 deletion on thymocyte selection varies depending on the transgenic TCR analyzed, ranging from a slight to a marked shift from positive toward negative selection. An explanation for the variable effect of CD5 on selection is suggested by the observation that CD5 sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
273
2
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 251 publications
(290 citation statements)
references
References 38 publications
10
273
2
2
Order By: Relevance
“…By analysis of CD2-GATA3 transgenic and Gata3 conditional knockout mouse models, as well as CD2-GATA3 transgenic mice that were crossed into various TCR-transgenic mice, we show in this report that GATA3 modulates the surface expression level of the glycoprotein CD5 and enhances TCR expression during CD4 T lineage development in vivo. The regulatory mechanisms that control CD5 expression are key to lymphocyte development and function, because CD5 is a negative regulator of TCR signaling during thymocyte development and therefore participates in the finetuning of the TCR repertoire [13][14][15][16]. Interestingly, because GATA3 is induced by TCR signaling [7], our finding that GATA3 controls TCR up-regulation and CD5 down-regulation implicates GATA3 in a positive feedback loop that increases TCR surface expression during CD4 T lineage development.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…By analysis of CD2-GATA3 transgenic and Gata3 conditional knockout mouse models, as well as CD2-GATA3 transgenic mice that were crossed into various TCR-transgenic mice, we show in this report that GATA3 modulates the surface expression level of the glycoprotein CD5 and enhances TCR expression during CD4 T lineage development in vivo. The regulatory mechanisms that control CD5 expression are key to lymphocyte development and function, because CD5 is a negative regulator of TCR signaling during thymocyte development and therefore participates in the finetuning of the TCR repertoire [13][14][15][16]. Interestingly, because GATA3 is induced by TCR signaling [7], our finding that GATA3 controls TCR up-regulation and CD5 down-regulation implicates GATA3 in a positive feedback loop that increases TCR surface expression during CD4 T lineage development.…”
Section: Introductionmentioning
confidence: 77%
“…As targeted deletion of CD5 has been shown to reduce DP cellularity in various TCR-transgenic models, including HY and DO11.10 [16,31], it is likely that the reduction of DP cell numbers in the CD2-GATA3 transgenic models is a result of decreased CD5 expression. As CD5 acts as a negative regulator of TCR-mediated signal transduction [13,16], reduction of CD5 expression levels in CD2-GATA3-expressing DP cells is expected to increase TCR signal strength, which will result in negative selection and thus deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial studies on CD5 À/À mice did not reveal major defects in T-cell development [44], further analysis using TCR transgenic mice showed that CD5 can influence the outcome of thymocyte selection depending on the avidity of the TCR-peptide/ MHC interaction. Thus, in the absence of CD5, thymocytes with high affinity TCR were negatively selected, likely due to increased TCRmediated signaling [43,45].Since selection of nTreg appear to require high affinity/avidity interactions [46], we hypothesized that CD5 might be involved in their generation. Here, we describe that the absence of CD5 leads to increased numbers of thymic and peripheral nTreg, accompanied by increased cell death of naïve thymocytes.…”
mentioning
confidence: 99%
“…Although initial studies on CD5 À/À mice did not reveal major defects in T-cell development [44], further analysis using TCR transgenic mice showed that CD5 can influence the outcome of thymocyte selection depending on the avidity of the TCR-peptide/ MHC interaction. Thus, in the absence of CD5, thymocytes with high affinity TCR were negatively selected, likely due to increased TCRmediated signaling [43,45].…”
mentioning
confidence: 99%